Reconstruction of NDVI based on Larix gmelinii tree-rings during June–September 1759–2021 - Li, Xiangyou; Wang, Zhaopeng; Luo, Taoran; Wang, Xinrui; Wang, Aiai; Zhang, Dongyou (Frontiers in Forests and Global Change, 2024)
Investigating the long-term dynamics in the canopy proves to be difficult due to the short observational records of the normalized difference vegetation index (NDVI). To explore the linkage between tree growth, NDVI dynamics and large-scale atmospheric circulation in the Greater Khingan Mountain, Northeast China, we established a chronology of Larix gmelinii tree ring width at three elevations (870–920 m, 1,100–1,150 m and 1,270–1,320 m) in the northern foothills of the mountain range. We then calculated the correlations between the tree ring chronologies and NDVI and climate factors, and reconstructed the NDVI time series from June to September 1759–2021 in the region based on the middle-elevation tree ring chronology. The results identify the positive effect of temperature (r = 0.56, p < 0.01) and the negative effect of precipitation (r = −0.44, p < 0.01) in the growing season as the main influencing factors of NDVI for the study period (1981–2019). The 11-year moving average of the reconstructed NDVI series reveals two periods of high canopy vigor (1898–1926 and 2009–2013) and three periods of low canopy vigor (1860–1962, 1882–1888 and 1968–1977) in the last 263 years. These periods correspond to drought events recorded in the historical literature. Wavelet analysis shows that the reconstructed sequences exhibited 11–13, 23–25, and 39–42 years period variations. Integrating this with spatial correlation analysis reveals that tree growth in the Mangui region was impacted by the combined effect of the North Pacific Decadal Oscillation and the North Atlantic Multidecadal Oscillation. The results of this paper provide a reference for the study of vegetation change patterns in the northern foothills of the Greater Khingan Mountains.